PERAN MASYARAKAT DAN PEMERINTAH DALAM PENGELOLAAN AIR LIMBAH DOMESTIK DI SUB DAS GAJAH WONG - , Muhammad Bayu Hartono ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Every human activities that use water will produce waste water. Waste water can contaminate the surrounding environment when it disposed directly into the environment without any treatment. It needs management over domestic waste water before disposed to the environment. The aims of this study are (1) knowing the domestic waste water management systems in Gajah Wong Sub Catchment, (2) examines the role of government and society in domestic waste water management, (3) to formulate alternative strategy of domestic waste water management. Using primary and secondary data with purposive sampling method to define research areas. Collecting primary data using observation and interviews techniques over 100 respondents using a questionnaire. Then for secondary data with literature studies. Technique of analysis data using qualitative and quantitative descriptive analysis, and for determine alternative strategies using SWOT matrix analysis. The results of this research indicate that domestic waste water management systems in the study area using septictank, wastewater treatment (IPAL), special tanks, and using ditch/drainage channels. There has been the role of government and citizens in managing domestic waste water such as the wastewater treatment (IPAL), communal septictank, public toilet, and greywater tank. Strategy of domestic waste water management are affirm the role and sanction, built pipe network,organize community self-help and routine contribution, use information technology, and increase the capacity of waste water management instalation.